PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA KELAS XI DI SMA NEGERI 10 KOTA JAMBI - Diliza Afrila, Elok Paiko, (SJEE (Scientific Journals of Economic Education), 2018)
This study aims to determine the description of respondents and the influence of the school environment on the motivation of studying students of class XI in SMA Negeri 10 Kota Jambi. Based on data analysis on the results of research that there is a significant influence between the school environment on student learning motivation XI in SMA Negeri 10 Kota Jambi. The results showed that (1) the school environment variables included in the category enough. This is indicated by the average of school environment variables is 3.93 withRespondent Achievement Level (TCR) of 78.69. Furthermore, learning motivation variables included in the category enough. This is indicated by the average of learning motivation variable is 3.80 with Respondent Achievement Level (TCR) equal to 76,06, and (2) school environment have an effect on signifikan to student's learning motivation. This is indicated by the Sig value. <0,05, that is 0,000 <0,05 and tcount> ttable, that is 11,300> 1,97601. Keyword : School Environment, Motivation Learning.